Post-Transcriptional Regulation of E2F Transcription Factors: Fine-Tuning DNA Repair, Cell Cycle Progression and Survival in Development & Disease - Dagnino, Lina; Singh, Randeep Kaur; Judah, David (IntechOpen, 2011)
None